Досвід Ізмаїльського державного гуманітарного університету в галузі впровадження освітніх інновацій - Андрея Певсе; Andreya Pevse; Pősze Andrea; Катерина Допополик; Dopopolyk Kateryna; Ірина Смирнова; Smyrnova Iryna (СумДПУ імені А. С. Макаренка, 2020)
Резюме. Відображений досвід Ізмаїльського державного гуманітарного університету в галузі впровадженнѐ освітніх інновацій і, особливо, у їх застосуванні з метоя підвищеннѐ мотивації здобувачів вищої освіти сприймати знаннѐ та генерувати нові. Описане впровадженнѐ освітніх інновацій в освітній процес здобувачів вищої освіти освітньо-професійної програми «Середнѐ освіта: трудове навчаннѐ та технології. Інформатика», першого рівнѐ вищої освіти на здобуттѐ освітнього ступенѐ бакалавр за спеціальністя 014 Середнѐ освіта, предметна спеціальність 014.10 Трудове навчаннѐ та технології, галузі знань 01 Освіта/Педагогіка, кваліфікаціѐ: Бакалавр освіти з трудового навчаннѐ та технологій. Учитель трудового навчаннѐ, технологій та інформатики.

Abstract. The problem of introducing educational innovations in educational establishments is analysed. The experience of Ismail State University of Humanities in introducing educational innovations and, especially, in applying them in order to increase the motivation of the applicants for higher education to absorb knowledge and generate new ones is reflected. Description of the introduction of educational innovations in the educational process of the applicants for higher education in the educational and vocational programme “Secondary education: vocational training and technology. Informatics”, the first level of higher education for obtaining an educational baccalaureate degree in the specialty 014 Secondary education, subject specialty 014.10 Vocational education and technology, field of knowledge 01 Education/Pedagogy, Qualifications: Bachelor of Education in Vocational Training and Technology. Teacher of vocational education, technology and informatics by teachers of the Department of Mathematics, Informatics and Information Activities of the Ismail State University of Humanities. Pedagogical conditions for the implementation of experimental research and ways of their introduction in educational process of higher education institutions are proposed. Modern information technologies have been identified to improve the quality of the educational process through the introduction of innovative technologies
Experience of Ismail State University of Humanities in introducing educational innovations
Keywords: освітні інновації; електронні освітні ресурси; інформаційне освітнє середовище; SMART-комплекси